“HOW GRAND IS OUR DESIGN FOR EUROPE?”: INTEGRATION PLANS OF THE GREAT BRITAIN IN THE LATE OF 1950S - E. V. Khakhalkina (Vestnik MGIMO-Universiteta)
The UK European Union membership referendum 2016 and its results actualized the study of the British initiatives in the sphere of integration before the entry into the European Economic Community in 1973. The article is devoted to the little-known in Russian historiography "Grand Design"of H. Macmillan, nominated in the wake of the failure of the Suez operation against Egypt in 1956. Plan with such bright and eye-catching name suggested the creation of a broad integration group in Europe as alternative with Britain as a leader to the preparing for the establishment of projects of the European Economic Community and the European Atomic energy community. The project was designed to restore the prestige of the Conservative Party and to strengthen the shaky position of Britain in NATO and European affairs after Suez Crisis. At the same time the emergence of the plan reflected the desire of the Prime Minister, Harold Macmillan to weaken the struggle inside political establishment between supporters and opponents of the country's full-fledged participation in the European integration and take the lead in the integration movement from France. Analysis of the content of the project and attempts to implement it within the framework of a Free Trade Area (FTA) reveals the essence of the "special position" of the UK towards supranational integration and the British vision of the future of European integration. Modern United Kingdom appeared in the new European realities after the Referendum on the country’s membership in the European Union and returns to the starting point on the path of supranational integration and to the search for its place in Europe. In these circumstances, the ideas expressed by British politicians more than half a century ago, may again prove to be demanded and relevant.